Treatment of micropollutants in water and wastewater - Virkutyte, Jurate; Varma, Rajender S.; Jegatheesan, Veeriah (IWA Publishing, 2010)
This book will give a comprehensive overview of modern analytical methods and will summarize novel single and hybrid methods to remove continuously emerging contaminants - micropollutants from the aqueous phase. This book will give a comprehensive overview of modern analytical methods and will summarize novel single and hybrid methods to remove continuously emerging contaminants - micropollutants from the aqueous phase.
Keywords: Sewage -- Purification.; Water -- Purification.; Micropollutants.; elektronické knihy; electronic books